Determinants of the Regular Physical Activity among Employees of Healthcare Network: Application of Health Belief Model - Reza Jorvand; Mahmoud Tavousi; Fazlollah Ghofranipour (Journal of Education and Community Health)
Background & Objective: Inactivity is one of the 10 leading causes of death in the world, doubling the risk of cardiovascular disease. Health belief model (HBM) is an effective model in predict the regular physical activity behavior. This study aimed at identifying determinants of the regular physical activity in order to prevent cardiovascular diseases, using HBM. Instruments & Methods: This descriptive-analytical cross sectional study was conducted on employees working in a healthcare network affiliated to Ilam University of Medical Sciences in 2017. 163 subjects were selected by simple random sampling method. The instruments to collect the data were standard inventory of HBM-ISCS and self-made questionnaire that were applied after reviewing and approving their validity and reliability. Eventually, the data were analyzed, by SPSS 16, using Pearson correlation coefficient, multiple regression analysis, and ETA test. Results: The perceived severity and self-efficacy were significant predictors of daily and weekly regular physical activity. Meanwhile, multiple regression analysis predicted 23.3% of the behavior. Also, gender had the strongest relationship with the barriers of physical activity and marital status and occupation had the strongest relationship with self-efficacy. Education had no significant statistical relationship with model constructs and age had a significant statistical relationship with perceived severity and the benefits of physical activity. Conclusion: The perceived severity and self-efficacy from health belief model are the strongest determinants for daily and weekly physical activity.